ROBERT FREESTONE, MARCO AMATI (eds.) - Exhibitions and the Development of Modern Planning Culture - Díez Medina, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
ROBERT FREESTONE, MARCO AMATI (eds.)Ashgate, Farnham, Inglaterra, 2014, 303 págs.Idioma: Inglés